Mobile Brain/Body Imaging of three-ball juggling: Dynamics of neurobehavioral interactions between motor execution and perception - Iversen JR (My University, 2025)
This project developed three-ball juggling as a neurobehavioral model of complex skill learning. Using new approaches to jointly analyze movement and brain activity, we present results from the MoBI analyses of thirteen jugglers of varying skill studied at normal gravity and behavioral showing that juggling training under simulated reduced gravity can enhance skill acquisition. Brain dynamics were assessed using spectro-temporal analysis of cortically resolved high-density scalp EEG referenced to timing events extracted from motion capture data. Using new methods for movement artifact rejection, it is possible to reliably extract spatially localized brain activity related to visual processing, spatial attention, multi-sensory integration and motor execution. In the parietal cortex, known to be involved in spatial processing, alpha-band robustly desynchronizes at the moment the thrown ball reaches its apex, a time thought to be critical for trajectory estimation required for the planning of the timing and location of the next catch. Accordingly, parietal activity demonstrates a clear biomarker of the trial-to-trial deviation of the ball’s apex position in a natural center-out body-centered coordinate frame. A notable finding is an unusually narrow-band activity between 70-80 Hz that shows periodic modulation with positive/negative peaks corresponding to contralateral/ipsilateral throws and sharp transitions corresponding to catches, suggesting a possible role in intra-hand coordination. Three-ball juggling is a promising example of a complex skill learning that can be studied with MoBI to provide insights into the dynamics of neurobehavioral interactions between motor execution and perception.